Reduplicative Words in English Vocabulary: A Literature-Based Analysis - Nabila Saprani Ritonga; Yolanda Vanesa Andrini; Juni Sharah Lubis; Diah Nanda Amelia Siregar; Nurazizah Nurazizah; Fadillah Nursakinah; Rizky Ananda (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2026)
This paper examines the use of reduplicative words in English vocabulary by analyzing their types, structural patterns, and communicative functions. The study employed a qualitative descriptive method through a library research approach using books, journal articles, and previous studies related to reduplication and morphology. The literature analysis indicates that English reduplicative words are generally classified into full reduplication, rhyming reduplication, and ablaut reduplication. Furthermore, reduplicative forms mainly function as expressive and stylistic elements used to convey emphasis, emotional expression, playfulness, and informal meaning in communication. The study concludes that reduplication remains a creative and meaningful feature of English vocabulary and communication. The study employed a qualitative descriptive design through library research by analyzing 18 scholarly sources related to reduplication and morphology.